RANCANG BANGUN SISTEM KEAMANAN PINTU RUMAH MENGGUNAKAN SENSOR RFID (RADIO FREQUENCY IDENTIFICATION) DAN TOUCH SENSOR BERBASIS ARDUINO UNO - Fachri Muhamad; Desy Kristyawati (Jurnal Ilmiah Teknik, 2022)
The current door lock system still uses conventional keys, making it less efficient for homes with many doors because there are too many keys to carry, besides conventional locks are easily opened by thieves. So that a more practical and efficient key is needed, from this statement the idea of making an automatic door unlock device with an RFID (Radio Frequency Identification) Sensor and a Touch Sensor by using an electronic ID card as a key to unlock the door is needed. RFID sensors and touch sensors are supporting components so that the device can be controlled. Solenoid door lock can open the door and unlock the door for 5 seconds via commands previously sent from the RFID sensor and touch sensor. And after that the door closed and locked. Based on the test results, it can be concluded that the simulation of the door safety device can operate properly, according to the design made. RFID reader is used to read the tag code on the electronic ID card. The solenoid can unlock the door if the electronic ID card tag code matches that registered with the Arduino lde program, when the door is closed the solenoid will lock the door within 5 seconds.